Survey of Current Practice Patterns in the Treatment of Early-Stage Endometrial Cancer. Issue 2 (February 2016) - Pereira, Elena B.; De, Brian; Kolev, Valentin; Zakashansky, Konstantin; Green, Sheryl; Dottino, Peter; Gupta, Vishal
Abstract : Objectives: Our aim was to assess current surgical practices and use of adjuvant therapy in the treatment of FIGO (International Federation of Gynecology and Obstetrics) stage I endometrioid endometrial cancer. Methods: A 19-question survey was developed and sent to all Society of Gynecologic Oncologist members by e-mail. Data were collected anonymously using Internet-based survey software. Respondents were asked questions regarding preoperative evaluation, surgical approach, lymph node dissection (LND), and adjuvant therapy. Results: A total of 1399 surveys were distributed, 320 (23%) members completed the survey. Ninety-seven percent of respondents were gynecologic oncologists or fellows, and 87% treat 30 or more endometrial cancer patients yearly. Respondents were more likely to order preoperative tests such as computed tomography abdomen/pelvis and CA-125 for biopsy-proven grade 3 disease versus grade 1 (82% vs 29%). Robot-assisted laparoscopy was the preferred surgical approach (66%), followed by conventional laparoscopy (21%). Twenty-six percent of respondents perform LND in all cases. Forty-eight percent describe their LND as complete, to the level of the inferior mesenteric artery. Adjuvant therapy was recommended more often with increasing myometrial invasion, tumor grade, and lymphovascular space invasion. Vaginal brachytherapy was the most commonly recommended adjuvant therapy for stage IA. For stage IB, grade 3, positive lymphovascular space invasion disease, respondents were more likely to combine vaginal brachytherapy with external beam radiotherapy and/or chemotherapy. Older patients were more likely to have adjuvant therapy in earlier stages of disease than younger patients. Conclusions: Our findings demonstrate that respondents are individualizing care based on preoperative, intraoperative, and pathologic findings. As expected, adjuvant treatment is recommended for patients with higher stage and grade disease. Robot-assisted hysterectomy and chemotherapy are now commonly used in the management of this disease. We anticipate that new trends will continue to emerge as results from additional studies become available.